Synthesis And Characterization Of New Oxazepines Derived From D-Erythroascorbic Acid - Mukhlus, A. A.; Al-Rawi, M. S.; Al-Dujaili, A. H.; Tomma, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The new schiff bases derived from D-erythroascorbic acid contaning heterocyclic unit were synthesized by condensation of D-erythroascorbic acid with aromatic amine (containing 1,3,4oxadiazole or 1,3,4-thiadiazole unit) in dry benzene using glacial acetic acid as a catalyst. Derythroascorbic acid [IV] was synthesized by four steps (Scheme 1), while the primary aromatic amine which is containing 1,3,4-oxadiazole [VII] or 1,3,4-thiadiazole [VIII] synthesized by the reaction of 4methoxy benzoyle hydrazine [VI] with 4-amino benzoic acid or by the reaction tuloic acid with thiosemicarbazide, respectively in the presence of POCl3. The new 1,3-oxazepine derivatives were obtained by addition reaction of Schiff bases with different anhydrides in dry benzene, The new 1,3oxazepine derivatives [XII]a-d- [XIV]a-d were synthesized by refluxing compound [IX] , [X] or [XI] with different anhydride (maleic, phthalic, naphthalic anhydride or pyromellitic dianhydride) in presence of dry benzene. The structure of synthesized compounds have been characterized by their melting points , elemental analysis and by their spectral data; FTIR , UV-Vis, Mass and (1HNMR , 13CNMR of some of them) spectroscopy . All the synthesized compounds have been screened for their antibacterial activities. They exhibited good antibacterial activity against Escherichia coli (G-) and Staphylococus aureus (G+) .